Cash vs. Digital (With Reference to India) - Harnal, Bharti (International Journal of Psychosocial Rehabilitation, 2020)
There has been a long journey of receipt and payment transactions. Beginning from the barter system by primitive/traditional/modern man, from coin to currency notes (cash), and now to digital transactions, and maybe further with some other way. Coins and paper currency have a long history, and there have been ups and downs in currency also. With advances in technology, now payments have started being made through technology. Cash is used in its physical form, while digital transactions are done on the internet through online means. There is no doubt that digital payments are moving fast, as they have made transactions easy and convenient to handle, technology has advanced, there are high levels of security, they are less expensive, and there are monetary benefits in the form of discounts on payments/cash-back facilities.But at the same time, digital is not free from many shortcomings. There will always be some people who will find themselves in difficulties with transition. Digital transactions do not suit the underprivileged and marginalized groups such as people below the poverty line, people staying in rural areas, and the elderly. In spite of the increase in digital transactions, demand for cash is also increasing. In this paper, an attempt has been made on cash and digital transactions. How the demonetization has affected India’s monetary transactions. Does cash hold an important position in India? Does cash still hold an important position, and can technology replace it fully?.